Distribution of foreign employees in Slovakia - Komornik Jozef; Smolen Jan; Dudić Branislav; Beresova Gabriela (Ekonomija: teorija i praksa, 2020)
This work analyses the structure of foreign workforce in Slovakia by job category and country of origin. The foreign employees were divided into 9 job categories by level of sophistication ranging from leading workforce in organizations to auxiliary and unskilled workers. It has been found that the majority of employees in more sophisticated job categories are coming to Slovakia from larger and more developed economies, while those less sophisticated positions in Slovakia are mostly filled with Romanian, Hungarian and Ukrainian nationals. A very important role in almost all categories, irrespective of proficiency level, is played by nationals from The Czech Republic. This shows that close economic ties between The Czech Republic and Slovakia are reflected also on the labor market. The findings of this study have important implications for the labor market in Slovakia, as it has been shown in many research studies so far, that immigrant labor composition impacts various labor market variables.